0529 Full Facemask Induced Upper Airway Obstruction During PAP Titrations: A Common Phenomenon Hindering PAP Treatment When Unrecognized And Indication For Combination Therapy With Oral Appliance Mandibular Stabilization. (27th April 2018) - Simmons, J H; Meskill, G J
Abstract: Introduction: Mandibular retraction from Full-face masks (FFM) is not commonly considered when treating OSA. Analysis of PAP titrations of our sleep lab shows patients using FFM's for PAP therapy often require higher pressure than when utilizing a nasal mask. When patients are switched post-titration from a nasal mask to a FFM's (typically to address oral pressure leakage), it is assumed that pressure requirements are the same irrespective of mask type. We have demonstrated numerous cases in which switching to a full facemask during the PAP titration study has resulted in higher PAP pressure requirements. Methods: We identified OSA patients in whom in-laboratory PAP titration studies were performed where nasal mask were used initially and provided resolution of OSA (AHI &lt 5), but in whom oral leak was observed and unresolved by the addition of a chinstrap. The patients were switched to FFM's during the titration study. Results: 10 cases were identified where after switching to FFM's the patients required PAP pressures 4+ cm H2O higher than what was observed as therapeutic with nasal masks. In some cases, the patient was switched back to a nasal mask with re-identification of lower PAP pressure requirements than with the FFM. Conclusion: Our observations have shown that it is common for patients to require markedly higher PAP pressures with FFM's compared with nasal masks. This increased pressure requirement is best explained by mandibular retraction that occurs with the full facemask due to applied strap pressure needed to create a mask seal around the chin when the chin becomes relaxed during sleep. Previous reports by Simmons describe improvements in PAP treatment with mandibular stabilization to prohibit mandibular retraction and the associated increase in airway obstruction. We will present more extensive statistical aspects of the occurrence on this phenomena and descriptive examples for teaching purposes, so others can become more sensitive to this phenomenon and recognize indications of combination therapy with mandibular stabilizing dental appliances. Support (If Any): N/A.